METHODOLOGY OF USING INNOVATIVE APPROACHES IN DEVELOPING MATHEMATICAL CREATIVITY OF HIGH SCHOOL STUDENTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article scientifically reveals educational methods aimed at developing mathematical creativity of high school students in the process of teaching mathematics and their effectiveness.